Ageing and Its Different Perspectives - Shinde, Vaibhav; Dhalwal, Kamlesh; Mahadik, K.R. (Pharmacognosy Reviews)
Ageing is universal but complex biological process characterized by impairment of various functions and decreased ability to respond stress whose manifestations are familiar and unambiguous. The population of world is ageing rapidly. With the rapid increase in the population of people 60 years of age and older, considerable research is being focused on how to prevent or delay ageing and age-related disabilities. Although, there are many theories to explain the ageing phenomenon, there is no inclusive explanation of ageing by any one theory and why the ageing process can vary so much in speed and quality from individual to individual. Various theories of ageing have been proposed like mitochondrial ageing theory, glycation theory of ageing, free radical induced damage, etc. In this review, we attempt to sight how major theories are revolving around free radical induced damage and they are indeed interrelated, along with some traditional remedies to give reader general sketch of ageing process.
Keywords: Ageing; Oxidative Stress; Glycation; Traditional Medicine